Does Financial Planning Moderate the Relationship between Productivity and Wellbeing of Sarawak Paddy Rice Farmer? - Azra, Tilai; Rayenda Khresna, Brahmana; Puah, Chin Hong (Malaysia Consumer and Family Economy Association, 2022)
Despite having a vital role in national food security, there is an inadequate emphasis on the smallholder paddy farmer’s productivity and wellbeing. Previous studies regarding productivity and wellbeing relationships have no consensus. This research offers financial planning as moderation in the issue of productivity and wellbeing for Sarawak’s paddy rice farmers. A face-to-face interview was carried out with 115 paddy farmers. We ran the OLS regression along with an instrumented regression to eliminate reverse causality effects. This study shows that wellbeing improves as productivity and financial planning progress. Farmers are less likely to achieve happiness when their health condition deteriorates. The moderating role of financial planning on the relationship between productivity and wellbeing is not statistically significant. Results indicate that productivity and happiness do not rely on financial planning for paddy farmers. The research provides a basis and guidelines for policymakers to create financial awareness and provide evidence for corresponding studies to determine the role of financial planning for agricultural farmers in both developed and developing countries.